Protection of the African lion: a critical analysis of the current international legal regime - Watts, Samantha (Institute of Marine and Environmental Law, 2015)
The African lion is in danger of rapid population decline and possible extinction in the near future. Two decades ago there was an abundance of African lions, roughly 100 000, on the continent. But at present there are less than 32 000, some even believe there to be as little as 15 000, left. This decline is mainly due to threats arising from habitat loss, retaliatory and traditional killing, the trophy hunting industry and trade related issues. Consequently, African lions are listed as 'vulnerable' on the International Union for Conservation of Nature Red List of Threatened Species. This listing is being contested by commentators who believe that the species now requires an 'endangered' status. African lion populations, and the threats to the species, extend across state boundaries. Therefore, international law is of particular importance in providing conservation and protection measures to the species. Creating conservation obligations at a global level, allows for more uniform action, implementation and enforcement of legislation at regional and local levels. This dissertation looks at each threat to the African lion population in detail. Then, an assessment is made as to whether there is an international legal regime pertaining to each of these threats, and whether that regime is adequate. There has been an increase in arguments that the international legal framework pertaining to the African lion is in fact unacceptable for the protection of the species. This dissertation provides some clarity on the current international and regional legal regime pertaining to the African lion, and addresses both the positive and negative aspects of this regime. Consequently, it is found that the international legal regime for the African lion is ineffective in achieving their protection and survival. Recommendations are made on what needs to change, and the best way forward, through an international legal lens. The security and viability of the African lion is uncertain, and legal protection of the species needs to be clear to start ensuring their survival in the future. African lions are already regionally endangered in some parts of Africa, and the threats to the species are only increasing. Therefore, it is obvious that some legal changes need to be made, to ensure greater protection of the African lion, at an international level.